Positively Valenced Stimuli Facilitate Creative Novel Metaphoric Processes by Enhancing Medial Prefrontal Cortical Activation - Subramaniam, Karuna; Beeman, Mark; Faust, Miriam; Mashal, Nira (Frontiers in Psychology, 2013)
A metaphor is a figure of speech in which a subject is symbolic of another unrelated object. In the present study, we examined neural patterns associated with both novel unfamiliar and conventional familiar metaphoric processing, and how these patterns are modulated by affective valence. Prior to fMRI scanning, participants received a list of word pairs (novel unfamiliar metaphors as well as conventional familiar metaphors) and were asked to denote the valence (positive, negative, or neutral) of each word pair. During scanning, participants had to decide whether the word pairs formed meaningful or meaningless expressions. Results indicate that participants were faster and more accurate at deciding that positively-valenced metaphors were meaningful compared to neutral metaphors. These behavioral findings were accompanied by increased activation in the medial prefrontal cortex (mPFC), posterior cingulate cortex (PCC), and the right inferior parietal lobe (IPL). Specifically, positively-valenced novel unfamiliar metaphors elicited activation in these brain regions in addition to the left superior temporal gyrus when compared to neutral novel metaphors. We also found that the mPFC and PCC mediated the processing of positively-valenced metaphors when compared to negatively-valenced metaphors. Positively-valenced conventional metaphors, however, elicited different neural signatures when contrasted with either neutral or negatively-valenced conventional metaphors. Together, our results indicate that positively-valenced stimuli facilitate creative metaphoric processes (specifically novel metaphoric processes) by mediating attention and cognitive control processes required for the access, integration and selection of semantic associations via modulation of the mPFC. The present study is important for the development of neural accounts of emotion-cognition interactions required for creativity, language and successful social functioning in general.